Monitoring agricultural production and stocks - Laborde Debucquet, David (International Food Policy Research Institute, 2020)
Vizualization based on USDA-PSD dataset by David Laborde (IFPRI). Support for this work was provided by the CGIAR Research Program on Policies, Institutions, and Markets.